Effect of Morphology of ϵ‐MnO2 on Hydrogen Peroxide Sensing. Issue 14 (10th April 2019) - Shen, Huanhuan; Huang, Jianzhi; Wei, Yubo; Guo, Xinrong; Wang, Min; Wang, Lishi
Abstract: In this work, solid spherical, solid cubic and hollow cubic MnO2 microparticles were successfully synthesized via a facile precursor conversion method. All the crystal structures were defined as rare ϵ‐phase. The ϵ‐MnO2 was modified onto the glassy carbon electrode (GCE) to fabricate sensor platform for hydrogen peroxide (H2 O2 ) determination. The catalytic activity of the prepared materials was demonstrated to be in the order: hollow cubes > solid cubes > solid spheres ϵ‐MnO2 . The higher electrochemical activity is related to the higher conductivity and more exposed highly active crystal planes instead of BET surface area, electrode active area and surface charge. Additionally, the cubic ϵ‐MnO2 possesses greater catalytic rate constant ( K ), which is approximately an order of magnitude higher than that of spherical morphology, due to the faster electron transfer rates caused by reduced contact resistance. The proposed sensor possesses the excellent sensitivity, selectivity and stability, and is successfully applied to determine H2 O2 in real sample. Abstract : Solid spherical, solid cubic and hollow cubic ϵ‐MnO2 microparticles were synthesized via a facile precursor conversion method. The ϵ‐MnO2 exhibits a morphology‐dependent performance towards the catalysis of H2 O2 . The cube‐like MnO2 displays a better catalytic performance and catalytic rate constant ( K ) than that of spherical morphology. This work offers a fundamental understanding of how the improvement of catalytic properties could be achieved by design the morphology of catalyst.